Reciprocal translocation 14q;21q in a patient with the Brachmann-de Lange syndrome. Issue 6 (December 1983) - Wilson, W G; Kennaugh, J M; Kugler, J P; Wyandt, H E
Abstract : A patient with the Brachmann-de Lange syndrome was found to have an apparently balanced de novo translocation 14q; 21q. The relationship between this uncommon translocation and the patient's phenotype is unclear. Although most patients with the Brachmann-de Lange syndrome have normal chromosomes, the possibility of aetiological heterogeneity, including some rare chromosomal abnormalities, cannot be dismissed.